Tectonic Evolution of the Chos Malal Fold-and-Thrust Belt (Neuquén Basin, Argentina) From (U-Th)/He and Fission Track Thermochronometry - Sánchez, Natalia Paola (2018)
In the southern central Andes at 37–38°S latitude, the Chos Malal fold-and-thrust belt (FTB), which results from the Late Cretaceous closure of the Neuquén Basin, has generated increasing interest because of its potential for hydrocarbon exploration. Using detailed field mapping, seismic reflection, and well data analysis, we have produced balanced cross sections, which combined with apatite and zircon (U-Th)/He, and fission track thermochronology from samples distributed along the FTB, bring new constraints on the chronology of the structural development of the Chos Malal FTB. Fully reset samples obtained from the Early Jurassic rocks at the bottom of the sedimentary sequence exposed in the Cordillera del Viento, a major basement-involved hinterland structure, permit to quantify its cooling rate from 5.4 ± 4.1 and 3.8 ± 3.2 °C/Ma between 70 and 55 Ma down to between 2.0 ± 1.3 and 1.3 ± 0.9 °C/Ma after 55 Ma until the present. Detrital apatite fission track ages from Late Jurassic and Early Cretaceous sandstones reveal that tectonically driven exhumation through basement-involved thrusting has occurred at ~15–7 Ma in both the inner and outer sectors of the FTB. Finally, the cooling and exhumation of the Las Yeseras-Pampa Tril basement-involved anticlines at the mountain front at ~9–7 Ma, slightly younger than previously assumed, suggests a normal sequence of faulting propagation. Our proposed thermostructural model of the Chos Malal FTB contributes to a better understanding of the tectonic evolution of this segment of the Andes.